COMPOSITION AND DISTRIBUTION OF Xanthomonas oryzae pv. oryzae PATHOTYPES, THE PATHOGEN OF RICE BACTERIAL LEAF BLIGHT IN INDONESIA - Sudir Sudir; Dini Yuliani (AGRIVITA, Journal of Agricultural Science, 2016)
This research aimed to determine the composition and pathotype distribution of Xanthomonas oryzae pv. oryzae (Xoo) in several rice producing centers in Indonesia during the growing season of 2010-2013. The studies were conducted into three phases of activities, namely: sampling and collection of infected leaves from the representative rice growing areas; isolation and purification of the Xoo isolates; and evaluation of composition and pathotype of Xoo on five rice differential varieties. Results indicated that a total of 2,658 isolates Xoo have been isolated from 10 provinces representing rice ecosystem in Indonesia during the growing season from 2010-2013. Evaluating these Xoo isolates against five differential varieties revealed that these Xoo isolates consisted of three pathotypes III, IV, and VIII with a total of 30, 36, and 34%, respectively. The data also indicated that two pathotypes III and IV were dominant in three provinces, while the pathotype VIII was dominant in four provinces. As mentioned previously, such information are useful in designing strategy of integrating components of technologies combined in the management of Bacterial leaf blight (BLB) occurrences in a particular endemic areas.